2000
DOI: 10.1111/j.1600-065x.2000.imr017513.x
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironmental influences on human B‐cell development

Abstract: Mammalian B-cell development can be viewed as a developmental performance with several acts. The acts are represented by checkpoints centered around commitment to the B-lineage and functional Ig gene rearrangement--culminating in expression of the pre-B-cell receptor (pre-BCR) and the BCR. Progression of cells through these checkpoints is profoundly influenced by the fetal liver and adult bone marrow (BM) stromal cell microenvironments. Our laboratory has developed a model of human B-cell development that util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 51 publications
2
41
0
Order By: Relevance
“…The supportive interaction of mesenchymal stromal cells with hematopoietic progenitors in the BM is well exemplified by the fundamental influence of the former cells on early B cell lymphopoiesis. In this context, it has been shown that the close interaction with BM stromal cells is crucial for the normal development of progenitor B cells and is supported by cytokines including interleukin-7 (IL-7), stem cell factor (SCF), Flt3 ligand, thymic stromal lymphopoietin (TSL) and CXCL12 (also known as stromal cell-derived factor-1, SDF-1) [20]. Responsiveness of B cell progenitors to cytokines requires the surface expression of the pre-B cell receptor (pre-BCR) [21] which is indispensable for pre-B cell survival, proliferation, differentiation and allelic exclusion.…”
Section: Msc and The Hsc Nichementioning
confidence: 99%
“…The supportive interaction of mesenchymal stromal cells with hematopoietic progenitors in the BM is well exemplified by the fundamental influence of the former cells on early B cell lymphopoiesis. In this context, it has been shown that the close interaction with BM stromal cells is crucial for the normal development of progenitor B cells and is supported by cytokines including interleukin-7 (IL-7), stem cell factor (SCF), Flt3 ligand, thymic stromal lymphopoietin (TSL) and CXCL12 (also known as stromal cell-derived factor-1, SDF-1) [20]. Responsiveness of B cell progenitors to cytokines requires the surface expression of the pre-B cell receptor (pre-BCR) [21] which is indispensable for pre-B cell survival, proliferation, differentiation and allelic exclusion.…”
Section: Msc and The Hsc Nichementioning
confidence: 99%
“…Here, the specific phenotype of B-CLL SP cells, which was formally validated by ABCG2 and BMI-1 expressions, 20,27 was nevertheless quite incomplete as lacking typical cell surface markers of immaturity (for example, CD34, CD127). 28 However, B-CLL is a malignant disease of phenotypically mature B cells, in which clonal progeny naturally lacks expression of immaturity antigens. 25 Likewise, SP cells from other mature B-cell malignant hemopathies, such as multiple myeloma, also present phenotypes inherent to the differentiation status of their non-malignant counterpart.…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow cells were obtained by flushing two femora and two tibiae with PBS. Erythrocytes were lysed with a 0.15 M NH 4 Cl, 10 mM KHCO 3 , 0.1 mM Na 2 EDTA, pH 7.2-7.4 solution (spleen, bone marrow, and e16.5 fetal liver) or were eliminated by centrifugation in Ficoll (e17.5 and e18.5 fetal liver). Cells were filtered through a nylon membrane (80-m pores) and counted.…”
Section: Flow Cytometric Analysismentioning
confidence: 99%
“…The second program occurs in nonhemopoietic cells, which establish with the lymphoid precursors a cross-talk that is essential for lymphopoiesis (3). Although a number of proteins that are secreted or involved in cell-cell contact to regulate B lymphopoiesis have been described (4), their regulation is poorly understood. The identification of transcription factors that control this second gene program is therefore an important step forward.…”
mentioning
confidence: 99%